Nutrition and Health Status of Children of Government Schools in Rural Areas of Hassan District - Mirajkar, Bharati C.; T., Narayanaswamy (International Journal of Bio-resource and Stress Management, 2019)
Nutrition and health in early stages of human life determine to a great extent, the physical and mental well being of a person. Malnutrition is an impairment of health resulting from deficiency of essential nutrients, and over nutrition, which is an excess of one or more nutrients. The present study was undertaken to assess the health and nutritional status of school children of rural areas by assessing their clinical health status. The field study was based on the observations of 208 children, 104 girls and 104 boys studying in five government primary/ upper primary and high schools in Hassan district. Clinical Nutrition Survey Chart developed by FAO/ WHO Expert Committee on Medical Assessment of Nutritional Status was used assesses the symptoms of nutrient deficiency. Anthropometric measurements viz. height and weight of the children were recorded using weighing balance and height measuring rod respectively to study the growth pattern of the children. It was observed from the results that majority of the children boys (82.69%) and girls (72.12%) from the age group 6-15 years were under weight. Only one girl was overweight among the total sample. The nutritional health analysis showed signs of deficiencies among the children. Nutritional deficiency signs and symptoms like mild angular stomatitis due to vitamin B deficiency, loss of luster of hair and skin indicates protein and energy deficiencies and chalky teeth shows calcium deficiency. To overcome this problem the school intervention programmes should be developed which include different foods in adequate quantity to supply all essential nutrients.